PENGARUH PEMBERIAN EKSTRAK UBI JALAR UNGU (IPOMOEA BATATAS L.) TERHADAP PENURUNAN KADAR TRIGLISERIDA SERUM TIKUS JANTAN GALUR WISTAR (RATTUS NOVERGICUS) YANG DIINDUKSI KUNING TELUR PUYUH - RIZKY KHAIRULIANI; IRFAN HAMDANI (LP2MTBM MAKARIOZ, 2020)
Dislipidemia can be lowered using statin-type drugs. Indonesian people have made use of various types of plants that can beused as alterative drugs such as purple sweet potatoes. Purple sweet potato extract can lower triglyceride levels byincreasing the activity of the enzyme lipoprotein lipase by reducing lipid peroxide. Various studies have done the sameresearch but the doses submitted vary between researchers. To determine the most effective dosage in this study. Thisresearch is True experimental research, using animal trials with the control group (-) of aquabidest administration, controlgroup (+) of quail egg yolk administration, P1 group of quail yolk + purple sweet potato extract dose 150mg/kgBB, group P2quail yolk + purple sweet potato extract dose 100mg/kgBB. After 14 days of treatment measured triglyceride levels betweengroups. Average control triglyceride levels (-) 60.17±3,312, control (+) 140.50±13,126, P1 96.67±2,160, P2 80.50±8,712.After the one way anova test (p=0.00) post hoct Test Games-Howell showed significant differences between the treatmentgroup K (-) with K (+), K(-) with P1, K(-) with P2, K(+) with P1, K(+) with P2, P1 with P2. The administration of purple sweetpotato extract for 14 days in male mice wistar strain induced quail egg yolk can lower serum triglyceride levels of male micewistar strain at a dose of 100mg/kgBB more effectively compared to a dose of 150mg/kgBB.